2019
DOI: 10.1016/j.niox.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-induced root architectural changes of rhizotron-grown B. napus correlate with a differential nitro-oxidative response

Abstract: Zinc-induced root architectural changes of rhizotron-grown B. napus correlate with a differential nitro-oxidative response, Nitric Oxide (2019), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 86 publications
2
21
0
4
Order By: Relevance
“…CAT activity in soil was determined according to Feigl et al (2019). A soil suspension (consisting of 2 g soil, 40 mL distilled water and 5 mL 0.3% H 2 O 2 solution) was incubated for 20 min, and then 5 mL 1.5 M H 2 SO 4 was added.…”
Section: Determination Of Soil Enzyme Activitymentioning
confidence: 99%
“…CAT activity in soil was determined according to Feigl et al (2019). A soil suspension (consisting of 2 g soil, 40 mL distilled water and 5 mL 0.3% H 2 O 2 solution) was incubated for 20 min, and then 5 mL 1.5 M H 2 SO 4 was added.…”
Section: Determination Of Soil Enzyme Activitymentioning
confidence: 99%
“…Leaching of contaminants from leaf litter is likely (Maunoury-Danger et al, 2018). Zn has been shown to increase fine root growth in some concentrations (Feigl et al, 2019), but we cannot explain why contaminated litter increased black oak seedling height. The negative response of autumn bent grass to any birch litter, whether contaminated or not, could be due to the high phenolic content of birch leaves (Keinänen et al, 1999) and might indicate that gray birch, regardless of its metal uptake, could have negative consequences for some early successional species.…”
Section: Discussionmentioning
confidence: 91%
“…The same rhizotron system was utilized as described in [4]. 15 cm wide, 30 cm tall, and 1.6 cm thick rhizotrons were assembled from plexi panels, polifoam sheets, and screws with wing nuts ( Figure S1).…”
Section: Rhizotron System Plant Material and Growing Conditionsmentioning
confidence: 99%
“…Nonetheless, plants try to minimize the adverse effect of HMs by either avoiding or excluding them. Dealing with the fate of HMs, many studies revealed that they affect a wide range of processes, including the disturbance of germination and early development, genotoxicity, disintegration of membranes, inactivating enzymes or even causing oxidative and nitrosative stress [4][5][6]. At low concentrations, HMs are able to trigger a positive adaptation mechanism called stress-induced morphogenic response, which is a special combination of inhibited longitudinal growth of the primary root and induced lateral root development [7], resulting in a shallower but more extensive root system with potentially better tolerance against HMs [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation